Using nested connectivity models to resolve management conflicts of isolated water networks in the Sonoran Desert. Issue 1 (11th January 2017) - Drake, Joseph C.; Griffis‐Kyle, Kerry; McIntyre, Nancy E.
Abstract: Connectivity is essential to organisms for dispersal, mate finding, and resource access. Management conflicts may arise if the attempts to maintain connectivity in the face of habitat loss result in opening up dispersal corridors to invasive species and disease vectors to already‐threatened native species. Using the mule deer ( Odocoileus hemionus ) and American bullfrog ( Lithobates catesbeianus ) as examples in a network of surface waters in the Sonoran Desert, we illustrate and propose a resolution to these conflicts. We used structural and functional metrics from graph and circuit theory to quantify landscape connectivity within a spatially nested framework under current and future climate‐based scenarios at regional and local scales to project structural and functional climate impacts for both species. Results indicated that climate impacts may reduce both structural and functional potential connectivity for each species. Mule deer, however, will be impacted to a lesser degree, and the proposed management mitigation of exclusion areas will have a potential lesser impact on this species. From our results, we propose a method to create exclusion areas and site new waters to help mitigate increasing spread of invasive species like the bullfrog while maintaining resource availability and local connectivity for economically important species like the mule deer. The isolation of local clusters from invasive species may be a successful and useful way to reduce management conflicts in the Sonoran Desert isolated waters network and beyond.